Case-control analysis of truncating mutations in DNA damage response genes connects TEX15 and FANCD2 with hereditary breast cancer susceptibility - Tuomo Mantere (Nature Portfolio, 2017)
Abstract Several known breast cancer susceptibility genes encode proteins involved in DNA damage response (DDR) and are characterized by rare loss-of-function mutations. However, these explain less than half of the familial cases. To identify novel susceptibility factors, 39 rare truncating mutations, identified in 189 Northern Finnish hereditary breast cancer patients in parallel sequencing of 796 DDR genes, were studied for disease association. Mutation screening was performed for Northern Finnish breast cancer cases (n = 578–1565) and controls (n = 337–1228). Mutations showing potential cancer association were analyzed in additional Finnish cohorts. c.7253dupT in TEX15, encoding a DDR factor important in meiosis, associated with hereditary breast cancer (p = 0.018) and likely represents a Northern Finnish founder mutation. A deleterious c.2715 + 1G > A mutation in the Fanconi anemia gene, FANCD2, was over two times more common in the combined Finnish hereditary cohort compared to controls. A deletion (c.640_644del5) in RNF168, causative for recessive RIDDLE syndrome, had high prevalence in majority of the analyzed cohorts, but did not associate with breast cancer. In conclusion, truncating variants in TEX15 and FANCD2 are potential breast cancer risk factors, warranting further investigations in other populations. Furthermore, high frequency of RNF168 c.640_644del5 indicates the need for its testing in Finnish patients with RIDDLE syndrome symptoms.